Strategi Peningkatan Pelayanan Istana Maimun Sebagai Warisan Budaya Melayu - Muhammad Rizki Lubis (Tourism, Hospitality And Culture Insights Journal, 2023)
Maimun Palace is the palace of the Sultanate of Deli which is one of the cultural and historical icons located in Medan City, North Sumatra. This research utilizes qualitative data obtained through observation at the Maimun Palace. Sources of research data were obtained through library research, and field observations (observations by participants) also provide important data about improving services at the Maimun Palace. These data are important data obtained from interview materials to support the author's argument. The purpose of this study is to analyze the challenges and obstacles in serving at Maimun Palace as a Malay cultural heritage and identify strategies that can be implemented to improve services at Maimun Palace and are expected to strengthen the attractiveness of Malay culture and increase visitor satisfaction at Maimun Palace. The results of the study indicate that it is recommended that Istana Maimun implement strategies such as providing adequate information, improving facilities for the convenience of visitors, and fostering authentic cultural interactions. This strategy aims to overcome the challenges faced in service delivery and increase visitor satisfaction. By providing quality services, Maimun Palace can create a positive experience for tourists, increase their level of satisfaction, and form a positive image for this tourist destination